POLYAMIDE - CUO NANOCOMPOSITE MEMBRANES USED FOR MEDICAL WASTEWATER AND E. COLI INHIBITION - Ion Ciuca; Kamel Earar; Oleg Solomon; Doriana Agop Forna; Carmen Tiutiuca (Romanian Society of Oral Rehabilitation, 2023)
The influence of different concentrations of CuO nanoparticles on the Polyamide (PA) membrane properties was studied. By adding CuO nanoparticles like additives to the membrane structure, the permeability increases for concentrations between 0.5 to 1.5 wt% nanoparticles and decreases for higher concentrations because of the aggregation phenomenon that appears. PA membranes were made using four different concentrations of CuO nanoparticles, 0.5, 1, 1.5 and 2 wt%. For membranes with more than 1.5 wt% nanoparticles a better inhibition effect of E coli on the membrane surface was observed after 12 and 24 hours. Porosity evolution is affected in the same way by the nanoparticles' concentration increasing for concentrations less than 1.5wt%. The separation of pollutants is a challenging task in wastewater from the industries in general and the medical sector in particular. PA membranes with CuO nanoparticles have better rejection properties. For methylene blue, rejection is increasing from 87% for membranes with 0.5 wt% nanoparticles to 99% for membranes with 2 wt% nanoparticles.